Actives Methodologies in Bilingual-Bicultural Education in Libras Literature Course of Federal University of Ceara: Students' perception - Nascimento, Antonio Daley Marques do (2021)
The present study aims to describe the perception of students of the Libras Literature course at the Federal University of Ceará regarding the use of active methodologies in the mediation of Bilingual-Bicultural education. This is a qualitative, descriptive Survey research, carried out from September 10th to 30th, 2020, with 24 students. As an inclusion criterion, it was adopted the condition of having experienced in person the actives methodologies in the mediation of learning, in the period from 2018.1 to 2019.2, in at least one of the five defined disciplines. The sample of 24 respondents was intentional, in the universe of 64 students that was distributed in 6 (25%) Deaf and 18 (75%) Hearing. A mixed digital questionnaire was applied through the Google Forms platform, containing 10 closed and 2 open questions, all in Portuguese and in Libras, for each of the seven Active Methodology techniques. The results point to the effectiveness of the techniques in the teaching and learning process of bilingual classes, especially in the consolidation of student autonomy and the development of criticality. A research is suggested to evaluate, in the same way, the students' perception regarding the use of Active Methodologies as strategies for learning assessment.